2014
DOI: 10.1134/s1070427214100255
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of (p-Vinylphenyl)cyclopropylmethyl cinnamate with styrene

Abstract: Radical copolymerization of (p-vinylphenyl)cyclopropylmethyl cinnamate with styrene was studied. A new cyclopropane-containing photosensitive copolymer was prepared. The composition and structure of the synthesized copolymer and the relative activity constants of the monomers were determined, and the Q-e parameters were calculated. The dependence of the photosensitivity on the copolymer composition was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It has been revealed that the absorption bands of the benzene and cyclopropane rings are retained in the compounds 9-12 and there are the absorption bands at 875 and 1250 cm -1 for fragment. In the IR spectra of 2-phenylcyclopropylcarbinols (5)(6)(7)(8) in the pure form, it is seen a strong absorption in the field of ~1050 cm -1 , which is probably characteristic for alcohols C-O group. The absorption of alcohols 5-8 is especially appeared as two broad bands: one at 3340 cm -1 and the second, relatively lowintensive at 3560 cm -1 .…”
Section: -12mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been revealed that the absorption bands of the benzene and cyclopropane rings are retained in the compounds 9-12 and there are the absorption bands at 875 and 1250 cm -1 for fragment. In the IR spectra of 2-phenylcyclopropylcarbinols (5)(6)(7)(8) in the pure form, it is seen a strong absorption in the field of ~1050 cm -1 , which is probably characteristic for alcohols C-O group. The absorption of alcohols 5-8 is especially appeared as two broad bands: one at 3340 cm -1 and the second, relatively lowintensive at 3560 cm -1 .…”
Section: -12mentioning
confidence: 99%
“…The observed band at 3500 cm -1 in the spectra of a dioxane solution of 2-phenylcyclopropylcarbinols (5)(6)(7)(8), is probably referred to the vibrations of hydroxyl groups forming hydrogen bonds between alcohol molecules in dimeric complexes and between alcohol molecules in dioxane. The bands at 3620 cm -1 , which appear as a result of some decrease of the concentration of closed dimeric complexes at dilution, probably can be attributed to the vibration of end hydroxyl group of the dimer type .…”
Section: -12mentioning
confidence: 99%
See 1 more Smart Citation